How the approval system affects Chinese scientific journals. Issue 4 (1st October 2013) - LIN, Songqing
ABSTRACT: Chinese scientific journals are moving in the right direction but developing first‐class academic journals still requires a number of obstacles to be overcome. Before the birth of any journal, a very complex journal approval system (JAS) must be negotiated. The paper will first present the history of the JAS in China and then analyze its effect on the scientific journal system. The JAS poses potential risks to the development of journals, and journal quantity rather than quality is the current priority. This needs to be changed and the JAS should be replaced by a journal registration system. Simultaneously, a system in which entry (start up) and closure, if required, is much easier than at present should be introduced, allowing the market to be the principal arbiter of success or failure.